2020
DOI: 10.1111/jdv.16727
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidities in pediatric alopecia areata

Abstract: Background Comorbidities are associated with higher health care costs, complex management, and poorer health outcomes. Identification and treatment of comorbid conditions in paediatric alopecia areata (AA) patients could provide an opportunity to improve health outcomes. Objectives To determine the prevalence of comorbidities among paediatric patients with AA using a large de-identified aggregated patient database. Methods This is a cross-sectional study using aggregated health record data through April 1, 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 18 publications
2
26
1
4
Order By: Relevance
“…Whether alopecia areata is an autoimmune disease still remains controversial 35 but many studies have shown that severe cases are associated with a systemic activation of the immune system 36–39 . While topic or local therapies may cause hair regrowth, they are unlikely to target the cause of the disease; the use of systemic therapy is recommended for those patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether alopecia areata is an autoimmune disease still remains controversial 35 but many studies have shown that severe cases are associated with a systemic activation of the immune system 36–39 . While topic or local therapies may cause hair regrowth, they are unlikely to target the cause of the disease; the use of systemic therapy is recommended for those patients.…”
Section: Discussionmentioning
confidence: 99%
“…Systemic therapy is advisable for moderate-to-severe alopecia areata due to its association with systemic activation of the immune system Whether alopecia areata is an autoimmune disease still remains controversial 35 but many studies have shown that severe cases are associated with a systemic activation of the immune system. [36][37][38][39] While topic or local therapies may cause hair regrowth, they are unlikely to target the cause of the disease; the use of systemic therapy is recommended for those patients. The specific therapy (i.e.…”
Section: 78%mentioning
confidence: 99%
“…Alopecia areata was associated with significantly increased prevalence of atopic dermatitis (17.4% vs. 2.2% in the control group) anaemia (7.7% vs. 2.4%), obesity (5.7% vs. 1.1%), vitamin D deficiency (5.1% vs. 0.4%), hypothyroidism (2.6% vs. 0.2%), vitiligo (1.4% vs. 0.04%), psoriasis (1.4% vs. 0.07%), hyperlipidaemia (1.4% vs. 0.2%) and depression (2.6% vs. 0.6%). 8 Studies on the gut microbiome in 30 patients with alopecia areata showed significant changes, with an enriched presence of Holdemania filiformis, Erysipelotrichacea, Lachnospiraceae, Parabacteroides johnsonii, Clostridiales vadin BB60 group, Bacteroides eggerthii and Parabacteroides distasonis. 9 Finally, alopecia areata may be associated with a profound psychosocial burden, a decreased quality of life, anxiety, depression, alexithymia and impaired sleep quality 10 Thus, we hypothesize that alopecia areata is a disease with significant systemic impact (or a systemic disease per se) and evaluation of treatment efficacy should include general health parameters in addition to hair regrowth.…”
Section: Systemic Aspects Of Alopecia Areata Comment To the Article Bmentioning
confidence: 99%
“…lichenification, oozing/weeping, erosions, xerosis, plaques, papules, follicular accentuation, lichenoid papules, prurigo nodules). 2,3 Big data reveal increase in AD burden with several comorbidities, both cutaneous 5 and systemic ones 6,7 AD shows itself with dysfunctioning immune and non-immune skin-barrier components. AD patients have a low compliance with long-term therapies and that may be due to the underrecognized psychiatric burden 8 occasionally relapsing for different stressful conditions such as COVID-19 outbreak.…”
Section: Introductionmentioning
confidence: 99%